Persepsi Mahasiswa Program Studi Pendidikan Kewarganegaraan Universitas Pamulang Terhadap Permenhub Nomor 83 Tahun 2021 Tentang Penyelenggaraan Angkutan Penumpang Umum Pada Kawasan Strategis Nasional - Magdalena Murniwati Zebua; Nurullita Sari (Jurnal Mahasiswa Karakter Bangsa, 2026)
Public transportation policy has a strategic role in supporting community mobility, including students as active users of transportation services. The implementation of Permenhub Number 83 of 2021 concerning the implementation of transportation of people with motor vehicles that are not on the route has caused various perceptions among students, especially related to ease of access, cost efficiency, and equitable distribution of services. This study aims to analyze the perception of PPKn FKIP students of Pamulang University towards the policy and its impact on mobility and transportation accessibility around campus. This study uses a qualitative phenomenological approach with 15 students. Data collection techniques through interviews, observations, and documentation. Data analysis was carried out through the process of open coding, axial coding, and selective coding to find the main themes of student perception. The results of the study show that this policy is perceived positively by some students because it provides easy access and cost efficiency, but others consider that the implementation of the policy is not even, especially in areas with limited transportation access. The main impact of the policy can be seen in the change in student mobility patterns towards the use of online transportation as a form of adaptation to public policy. This study concludes that the policy has not fully met the principles of equity and efficiency of public transportation in the higher education environment. Therefore, it is necessary to optimize policies based on the regional context and increase student participation as young citizens in the process of evaluating public transportation policies.